A low-carbohydrate, high-fat diet leads to unfavorable changes in blood lipid profiles compared to carbohydrate-rich diets with different glycemic indices in recreationally active men - Kripp, Anna Maria; Feichter, Andreas; König, Daniel (Frontiers in Nutrition, 2024)
Objective: In addition to recent discussions of low-carbohydrate, high-fat diets (LCHF) from a performance perspective, there is a paucity of knowledge regarding influence of the combined effect of an exercise and nutritional intervention, which varies in carbohydrate (CHO) intake and glycemic indices, on blood lipid levels in recreationally active men.Methods: A total of 65 male runners (VO2 peak = 55 ± 8 mL•min -1 •kg -1 ) completed a 10-week ad libitum nutritional regimen (LOW-GI: ≥ 65% low GI CHO per day, n = 24; HIGH-GI: ≥ 65% high GI CHO per day, n = 20; LCHF: ≤ 50g CHO daily, n = 21) with a concurrent prescribed endurance training intervention. Fasting total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) were determined before and after the intervention. Additionally, 24-hour dietary recalls were completed twice weekly.Results: Following the intervention, TC was significantly higher in LCHF (196 ± 37 mg•dL -1 ) compared to both LOW-GI (171 ± 41 mg•dL -1 ) and HIGH-GI (152 ± 28 mg•dL -1 , p < 0.001). Additionally, LDL-C levels increased in LCHF (+17 ± 21 mg•dL -1 , p = 0.001), while they decreased in both CHO groups (p < 0.05, respectively). Only the HIGH-GI group demonstrated a significant reduction in HDL-C (-3 ± 9 mg•dL -1 , p = 0.006), while a decrease in TG was only significant in LOW-GI (-18 ± 36 mg•dL -1 , p = 0.008).Although mean blood lipid levels remained within the normal range, the data indicate that a low-carbohydrate, high-fat (LCHF) diet leads to unfavorable changes in individual blood lipid profiles compared to carbohydrate-rich diets. Therefore, it is recommended that the impact of a lowcarbohydrate diet on blood lipids be considered when counseling active and healthy individuals.